Akomodasi Komunikasi dalam Culture Shock Mahasiswa Patani Thailand - Safril Safril (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
This study aims to reveal the form of culture shock faced by students Patani Thailand as well as reveal the accommodation process communication convergence and divergence in which students Patani in UIN Sunan Gunung Jati Bandung. This type of research is qualitative and uses the method of Phenomenology. From these results obtained Patani students experience culture shock in the aspect of psychological and social aspects. Students Patani perform communication accommodation consist of pre, and post-process communication convergence and divergence accommodation is composed of verbal and non-verbal. The conclusion of this study is Patani Student 2015-2016 at the State Islamic University Sunan Gunung Jati Bandung experiencing Culture Shock, but they can be overcome by making accommodation communication convergence and divergence is quite effective so that they can survive (survive) and accepted by society in new environment that facilitate their purpose in Bandung is to study.